2013
DOI: 10.1249/mss.0b013e318298b19a
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Exercise-Induced Laryngeal Obstruction in Athletes

Abstract: In athletes with unexplained respiratory symptoms, EILO is an important differential diagnosis not discerned from other etiologies by clinical features. These findings have important implications for the assessment and management of athletes presenting with persistent respiratory symptoms despite asthma therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
179
3
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 163 publications
(199 citation statements)
references
References 29 publications
13
179
3
4
Order By: Relevance
“…3 Another study has shown that EILO may be as prevalent as exercise-induced bronchoconstriction, explaining 'treatmentrefractory' symptoms in around a quarter of young athletic patients referred with exertional respiratory symptoms. 4 Nielsen et al found EILO coexisting with exerciseinduced bronchoconstriction in just over 10% of individuals, perhaps explaining why 'partial' resolution of symptoms is seen in some young patients treated with inhaler therapy. 4 …”
Section: Prevalencementioning
confidence: 99%
See 2 more Smart Citations
“…3 Another study has shown that EILO may be as prevalent as exercise-induced bronchoconstriction, explaining 'treatmentrefractory' symptoms in around a quarter of young athletic patients referred with exertional respiratory symptoms. 4 Nielsen et al found EILO coexisting with exerciseinduced bronchoconstriction in just over 10% of individuals, perhaps explaining why 'partial' resolution of symptoms is seen in some young patients treated with inhaler therapy. 4 …”
Section: Prevalencementioning
confidence: 99%
“…4 Nielsen et al found EILO coexisting with exerciseinduced bronchoconstriction in just over 10% of individuals, perhaps explaining why 'partial' resolution of symptoms is seen in some young patients treated with inhaler therapy. 4 …”
Section: Prevalencementioning
confidence: 99%
See 1 more Smart Citation
“…An experienced specialist, who did not take part in performing the tests, scored the degree of EILO as none, mild, moderate or severe, using the scoring system developed by Maat and colleagues [17]. Several studies, including our previous work and the present study classify moderate and severe grades of EILO as clinically significant, and consider mild supraglottic EILO to be a variant of normal [3,7,9,10].…”
mentioning
confidence: 88%
“…In recent years, the emergence of exercise laryngoscopy [4] has led to a better understanding of laryngeal movement during exercise, and inspiratory supraglottic collapse on exertion has been established as a common cause of exertional breathlessness [5] that is correlated with exercise intensity [6]. Both glottic and supraglottic inspiratory closure are more commonly seen in females and most often in adolescents or young adults [7][8][9][10][11]. This predominance has yet to be explained; however, gender differences in larynx size/growth and consequently higher "Bernoulli forces" in females for a given respiratory demand could be a contributing factor [5].…”
mentioning
confidence: 99%